2019
DOI: 10.5539/ijms.v11n3p87
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of the Service, Superior Value Generator in the Restaurant Sector

Abstract: The purpose of this study is to analyze the effects of quality service on the image and the reputation obtained in restaurants. We also analyze the effect that the business image has on the reputation of restaurants. Finally, we want to discover the mediation effect of the image between the quality service and the reputation of the restaurants. This research is based on a sample of 202 consumers of five restaurants (franchise type) in the city of Guaymas Sonora, Mexico. The data collection was conducted during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 104 publications
(144 reference statements)
0
2
0
Order By: Relevance
“…Lastly, other studies have analyzed different antecedents of restaurant reputation, for example, the experience quality [3,25] and rituals in the workplace of employees [66]. However, our results uncover new reputational antecedents related to healthy and sustainable environments.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Lastly, other studies have analyzed different antecedents of restaurant reputation, for example, the experience quality [3,25] and rituals in the workplace of employees [66]. However, our results uncover new reputational antecedents related to healthy and sustainable environments.…”
Section: Discussionmentioning
confidence: 64%
“…These establishments must also intensify their reputation's effect on customers' responses to the experiences provided. Previous studies have found that the experience quality can help build a reputation and that this, in turn, can indicate perceived quality to potential clients [3,25], which ensures a restaurant's popularity grows due to word of mouth [26].…”
Section: Literature Reviewmentioning
confidence: 99%